TA`TSIIRU THARIIQAH AL-IMLA` AL-MANDZUUR LIMAHARAH KITAABAH AL-LUGHAH AL-‘ARABIYYAH LIDAA TALAAMIIDZ LISHAFI AT-TSAMIN AL-MADRASAH AT-TSANAWIYYAH DARUL MUSTAQIM PAMIJAHAN BOGOR FII AL-‘AAMI AD-DIRAASII 2022/2023 - Raodotul Jannah; Lukman Taufik Akasahtia; Usman (SHAWTUL ARAB, 2023)
This research is based on the background that methods are important in the learning process. One of them is imla' manzhur method with LCD Projector Media as an innovation in the use of learning methods and media. The application of the Imla' Manzhur method begins with the teacher displaying the imla' material and students pay attention to the material on the LCD with a predetermined time of 30 seconds, after finishing 30 seconds the teacher closes the writing on the LCD and students are welcome to write it on the answer sheet provided. To find out the influence of the Imla' manzhur method in improving Maharah Al-Kitabah Arabic language learning to students at MTs Daarul Mustaqiem Pamijahan Bogor and this research is based on quantitative research with the type of Pre-Experimental Design research, the population of this research is class VIII students and uses experimental method, there are also instruments in collecting information using Tests, and documentation. Based on the results of this research, it shows that after the application of the imla' manzhur method, the average value has increased from 62.5 to 80.2. And the magnitude of t obtained in the calculation listed at the calculated is greater than in the table t (t count>table) where t count = 21.93 while table t= 1.691 hereby the hyipothesis is accepted.